2015
DOI: 10.1111/trf.13239
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of hematopoietic stem cell yield after mobilization with granulocyte–colony‐stimulating factor in healthy unrelated donors

Abstract: The model allows the identification of female donors who eventually have a significant risk of harvest failure if requested to donate for recipients with a high body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 32 publications
2
41
1
Order By: Relevance
“…In the European set, only BMI correlated with circulating CD34+ cell counts. The mechanism behind association between higher BMI and better mobilization potential has been attributed to the effect of adipose tissue-containing HSCs, or a simple dose effect of G-CSF [8]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the European set, only BMI correlated with circulating CD34+ cell counts. The mechanism behind association between higher BMI and better mobilization potential has been attributed to the effect of adipose tissue-containing HSCs, or a simple dose effect of G-CSF [8]. …”
Section: Discussionmentioning
confidence: 99%
“…There is wide inter-individual variability in response to mobilization, and the outcome is hardly predictable despite several known demographic or clinical risk factors such as the following: age, sex, body mass index (BMI), ethnicity, diagnosis, and extent and duration of prior chemotherapy [48]. Inter-individual variation of HSC mobilization yield can be explained by a multifactorial model consisting of environmental and multiple genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors such as iron status have been recently evaluated . However, factors identified in these cohorts have not explained more than a 20%‐30% of the variability observed …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had indicated that there is an inter‐individual variation in progenitor cell mobilization among healthy subjects. It has also been reported that donor's sex, age, weight, white blood cell (WBC) and platelet count, among others, correlate with the CD34+ cell yield . Other factors such as iron status have been recently evaluated .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is desirable to have a reliable prediction method in order to avoid unnecessarily prolonged collection for the safety of donors. Some prediction methods have been proposed and have proven useful [14,15]. In the present study, we introduced a simple method to predict PBSC yield based on pre-CD34 count.…”
Section: Introductionmentioning
confidence: 99%